Effect of spineless-cactus mucilage on the in vitro rumen fermentation of cellulose, starch, and protein - Pinho,Ricardo Martins Araujo (2017)
SUMMARY The aim of this study was to evaluate the effect of the levels of spineless-cactus mucilage on the in vitro rumen fermentation of cellulose, starch, and protein. A completely randomized experimental design was adopted with a 5 × 3 factorial arrangement consisting of five levels of spineless-cactus mucilage (0, 5, 10, 20, and 40%) and three substrates (carboxymethylcellulose, starch, and trypticase). Treatments were evaluated in a ruminal environment simulated by in vitro incubation at different times of assessment: 0, 3, 6, 12, 24, and 48 h. The incubation procedure was repeated three times, totaling three evaluations per incubation time for each treatment. There was an interaction (P<0.05) between the mucilage levels and substrate for all evaluated ruminal parameters, except for the concentration of microbial protein after 48 h of fermentation and for the proportions of acetate and butyrate fermentation at time 0 h. There was a quadratic increase (P<0.05) in the concentration of ammoniacal nitrogen after 48 h of incubation in the media containing carboxymethylcellulose and trypticase. pH values decreased quadratically (P<0.05) as a function of the mucilage levels in the media containing carboxymethylcellulose and trypticase. Overall, no expressive alterations were observed between the individual molar proportions of acetate, propionate, and butyrate with the addition of spineless-cactus mucilage levels to the different substrates. Spineless- cactus mucilage affects the pattern of fermentation of starch, cellulase, and protein performed by rumen microorganisms.